MnTBAP Inhibits Bleomycin‐Induced Pulmonary Fibrosis by Regulating VEGF and Wnt Signaling. Issue 3 (26th September 2016) - Venkatadri, Rajkumar; Iyer, Anand Krishnan V.; Ramesh, Vani; Wright, Clayton; Castro, Carlos A.; Yakisich, Juan S.; Azad, Neelam
Abstract : Cellular oxidative stress is implicated not only in lung injury but also in contributing to the development of pulmonary fibrosis. We demonstrate that a cell‐permeable superoxide dismutase (SOD) mimetic and peroxynitrite scavenger, manganese (III) tetrakis (4‐benzoic acid) porphyrin chloride (MnTBAP) significantly inhibited bleomycin‐induced fibrogenic effects both in vitro and in vivo. Further investigation into the underlying mechanisms revealed that MnTBAP targets canonical Wnt and non‐canonical Wnt/Ca2+ signaling pathways, both of which were upregulated by bleomycin treatment. The effect of MnTBAP on canonical Wnt signaling was significant in vivo but inconclusive in vitro and the non‐canonical Wnt/Ca2+ signaling pathway was observed to be the predominant pathway regulated by MnTBAP in bleomycin‐induced pulmonary fibrosis. Furthermore, we show that the inhibitory effects of MnTBAP involve regulation of VEGF which is upstream of the Wnt signaling pathway. Overall, the data show that the superoxide scavenger MnTBAP attenuates bleomycin‐induced pulmonary fibrosis by targeting VEGF and Wnt signaling pathways. J. Cell. Physiol. 232: 506–516, 2017. © 2016 Wiley Periodicals, Inc. Abstract : In this study, we investigated the anti‐fibrotic effects of MnTBAP, a MnSOD mimetic on bleomycin‐induced pulmonary fibrosis. We demonstrate that MnTBAP significantly inhibits bleomycin‐induced fibrogenic changes both in vitro and in vivo. We demonstrate that bleomycin induced upregulation of canonical Wnt and non‐canonical Wnt/Ca2+ signaling pathways that were targeted by MnTBAP. We present first‐hand evidence of the non‐canonical Wnt/Ca2+ signaling pathway being the predominant pathway in bleomycin‐induced pulmonary fibrosis. Furthermore, we report a novel crosstalk regulation in bleomycin‐induced pulmonary fibrosis in which VEGF was found to be upstream of Wnt signaling.